Electron Energy Spectrum and Auroral Power Estimation From Incoherent Scatter Radar Measurements. Issue 8 (22nd August 2018) - Virtanen, Ilkka I.; Gustavsson, Björn; Aikio, Anita; Kero, Antti; Asamura, Kazushi; Ogawa, Yasunobu
Abstract: Differential energy flux of electrons precipitating into the high‐latitude ionosphere can be estimated from incoherent scatter radar observations of the ionospheric electron density profile. We present a method called ELSPEC for electron spectrum estimation from incoherent scatter radar measurements, which is based on integration of the electron continuity equation and spectrum model selection by means of the Akaike information criterion. This approach allows us to use data with almost arbitrary time resolutions, enables spectrum estimation with dense energy grids, avoids noise amplifications in numerical derivatives, and yields statistical error estimates for all the output parameters, including the number and energy fluxes and upward field‐aligned currents carried by the precipitating electrons. The technique is targeted for auroral energies, 1–100 keV, which ionize the atmosphere mainly between 80 and 150 km altitudes. We validate the technique by means of a simulation study, which shows that Maxwellian, kappa, and mono‐energetic spectra, as well as combinations of those, can be reproduced. Comparison study for two conjugate satellite measurements to the EISCAT UHF radar are shown, for Reimei and Swarm, showing an agreement with the results. Finally, an example of a 2‐hr measurement by the EISCAT radar is shown, during which we observe a variety of precipitation characteristics, from soft background precipitation to mono‐energetic spectra with peak energies up to 60 keV. The upward field‐aligned current varies from 0 to 10 μ Am −2 and the total energy flux from 0 to 250 mWm −2 . Key Points: Electron energy spectra are estimated from incoherent scatter radar measurements by integrating the electron continuity equation Estimates of upward field‐aligned current and auroral power are integrated from the spectrum estimates The results are validated using simulations and comparisons with satellite measurements